Televisão e mídias digitais na América Latina: um cenário em construção - Gobbi, Maria Cristina [UNESP]; Machado Filho, Francisco [UNESP] (Sociedade Brasileira de Estudos Interdisciplinares da Comunicação (INTERCOM), 2015)
The text is the initial result of a project called Global iTV, Interactive and systems Hybrid TV: a new advanced scheme for future services and applications in a global environment, contemplated by Call MCTI / CNPq 13/2012 – EUBrazil Cooperation Program in the field of Information and Communication Technologies (ICT) which has as its central theme the development of a standard that enables interoperability between the various digital TV systems operating jointly, exchanging and using information. Thus, using bibliographical and documentary research, the article goes on to demonstrate how this perspective panorama is drawing from the advent of digital television and the use of technology in Latin America, seeking to identify similarities, differences, problems and solutions arising from the use and consumption of digitizing television signal in the region. The results demonstrate the importance of media convergence, but point out that there are still large sections of the population on the margin of the Digital Society and the benefits provided by digital networks and that poverty and poor education are important contributions to this scenario.

El texto es el resultado inicial de un proyecto llamado Global iTV, Interactive and Hybrid TV systems: a new advanced scheme for future services and applications in a global environment, contemplada por MCTI / CNPq 13/2012 - Programa de Cooperación Brasil - EU dirigida al área de la información y la comunicación (TIC), que tiene como tema central el desarrollo de un modelo que permite la interoperabilidad entre los distintos sistemas de televisión digital que operan de manera conjunta, el intercambio y uso de información. Por lo tanto, utilizando investigación bibliográfica y documental, va a demostrar cómo este panorama perspectiva está llegando desde el advenimiento de la televisión digital y el uso de la tecnología en América Latina, tratando de identificar las similitudes, diferencias, problemas y soluciones que surgen del uso y consumo de la digitalización señal de televisión en la región. Los resultados demuestran la importancia de la convergencia de los medios, pero señalan que todavía hay grandes sectores de la población en la región que están al margen de la sociedad y de los beneficios proporcionados por las redes digitales y que la pobreza y la baja escolaridad son importantes contribuciones de este escenario.

O texto é resultado inicial do projeto denominado Global iTV, Interactive and Hybrid TV systems: a new advanced scheme for future services and applications in a global environment, contemplado pela Chamada MCTI/CNPq nº 13/2012 – Programa de Cooperação Brasil – União Europeia, direcionado para a área de Tecnologias da Informação e Comunicação (TIC), que tem como mote central desenvolver um padrão que possibilite a interoperabilidade dos diversos sistemas de TV Digital a operarem de forma conjunta, trocando e utilizando informações. Assim, utilizando pesquisa bibliográfica e documental, o artigo caminha na perspectiva de demonstrar como esse panorama está desenhado a partir do advento da televisão digital e do uso da tecnologia na América Latina, buscando apontar semelhança, diferenças, problemas e soluções advindos do uso e consumo da digitalização do sinal de televisão, na região. Os resultados demonstram a importância da convergência midiática, mas apontam que ainda há extensas camadas da população na região que estão a margem da Sociedade Digital e dos benefícios propiciados pelas redes digitais e que a pobreza e a baixa escolaridade são contributos importantes desse cenário.
Television and digital media in Latin America: a scenario under construction
Televisión y medios digitales en América Latina: un escenario en construcción
Keywords: Latin America; iDTV; Digital inclusion; Social inclusion; Digital media; América Latina; TVDi; Inclusão digital; Inclusão social; Mídias digitais